Wharton’s Jelly Mesenchymal Stem Cell Conditioned Medium Ameliorates Diabetes-Induced Testicular Damage and Sperm Abnormalities by Mitigating Oxidative Stress, Apoptosis, and Inflammation - Mojtaba Sargazi; Narges Karbalaei; Saied Karbalay-Doust; Sara Keshtgar; Zohre Aghaei (Stem Cells International)
Diabetes leads to testicular damage and infertility. Mesenchymal stem cells and their secretory trophic factors have shown potential as regenerative therapies for diabetes and its associated complications. This study examined the effects of conditioned medium derived from Wharton’s jelly mesenchymal stem cells (WJMSCs-CM) on sperm parameters, reproductive hormones, biochemical parameters, and histological changes in the testes of diabetic rats. Fifty-six male Sprague–Dawley rats (250–300 g) were assigned to eight groups: control, diabetes, and six diabetic groups receiving early or late treatments with WJMSCs-CM (D-CME, D-CML), insulin (D-INSE, D-INSL), or DMEM (D-DME, D-DML). In the early treatment groups, insulin (3 U/day, subcutaneously) and WJMSCs-CM (10 mg/week, intraperitoneally) were administered immediately after diabetes induction; in the late treatment groups, these interventions began 30 days postinduction. Blood glucose and insulin levels, along with sperm parameters, were assessed. Sex hormones, testicular antioxidant enzyme activity, malondialdehyde (MDA), and glutathione (GSH) concentrations were measured using colorimetric methods. Real-time PCR detected Bax, Bcl-2, and tumor necrosis factor-alpha (TNF-α) gene expression. Our results showed that diabetes increased blood glucose levels, decreased insulin and sex hormone levels, induced testicular oxidative stress and apoptosis, and reduced sperm parameters compared to the control. WJMSCs-CM significantly ameliorated hyperglycemia, increased insulin and sex hormone levels, and improved sperm quality. In WJMSCs-CM-treated diabetic rats, MDA levels were reduced, while GSH and antioxidant enzyme activity increased. Furthermore, WJMSCs-CM decreased the testicular Bax/Bcl-2 ratio and TNF-α expression, as well as enhanced spermatogenic, Sertoli, and Leydig cells. In conclusion, WJMSC-CM administration effectively mitigated diabetes-induced testicular damage by reducing oxidative stress, inflammation, and apoptosis. Early treatment with WJMSCs-CM was more effective than late treatment for diabetes-induced reproductive dysfunction.